(3YhGQa GdeYGQas - (3TgGH GdOjf CHh MaU YeQ Hf eMeO Hf YHO Gddg GdSgQhQOj GdTGaYj, GdSgQhQOj,J (B632 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYXje TCfg Gdbhi SdWGfg GdHGH GdChd ai PcQ efTC Ydhe GdUhajI s
(3BNQgG (B:s
(3jfJgi HChd GdHGH GdKGfi hGdNeSjf ai COH GdTjN heG jYJeO eY GdCUMGH hGdJdGePI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1177s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs